CRISPR-mediated activation of endogenous gene expression in the postnatal heart - Schoger, Eric; Doroudgar, Shirin (Circulation research, 2020)
Rationale: Genome editing by CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 is evolving rapidly. Recently, second-generation CRISPR/Cas9 activation systems based on nuclease inactive dead (d)Cas9 fused to transcriptional transactivation domains were developed for directing specific guide (g)RNAs to regulatory regions of any gene of interest, to enhance transcription. The application of dCas9 to activate cardiomyocyte transcription in targeted genomic loci in vivo has not been demonstrated so far. Objective: We aimed to develop a mouse model for cardiomyocyte-specific, CRISPR-mediated transcriptional modulation, and to demonstrate its versatility by targeting Mef2d and Klf15 loci (2 well-characterized genes implicated in cardiac hypertrophy and homeostasis) for enhanced transcription. Methods and Results: A mouse model expressing dCas9 with the VPR transcriptional transactivation domains under the control of the Myh (myosin heavy chain) 6 promoter was generated. These mice innocuously expressed dCas9 exclusively in cardiomyocytes. For initial proof-of-concept, we selected Mef2d, which when overexpressed, led to hypertrophy and heart failure, and Klf15, which is lowly expressed in the neonatal heart. The most effective gRNAs were first identified in fibroblast (C3H/10T1/2) and myoblast (C2C12) cell lines. Using an improved triple gRNA expression system (TRISPR [triple gRNA expression construct]), up to 3 different gRNAs were transduced simultaneously to identify optimal conditions for transcriptional activation. For in vivo delivery of the validated gRNA combinations, we employed systemic administration via adeno-associated virus serotype 9. On gRNA delivery targeting Mef2d expression, we recapitulated the anticipated cardiac hypertrophy phenotype. Using gRNA targeting Klf15, we could enhance its transcription significantly, although Klf15 is physiologically silenced at that time point. We further confirmed specific and robust dCas9VPR on-target effects.Conclusions: The developed mouse model permits enhancement of gene expression by using endogenous regulatory genomic elements. Proof-of-concept in 2 independent genomic loci suggests versatile applications in controlling transcription in cardiomyocytes of the postnatal heart.